Analysis of bacterial and fungal communities in Marcha and Thiat, traditionally prepared amylolytic starters of India - Shankar Prasad Sha (Nature Portfolio, 2017)
Abstract Marcha and thiat are traditionally prepared amylolytic starters use for production of various ethnic alcoholic beverages in Sikkim and Meghalaya states in India. In the present study we have tried to investigate the bacterial and fungal community composition of marcha and thiat by using high throughput sequencing. Characterization of bacterial community depicts phylum Proteobacteria is the most dominant in both marcha (91.4%) and thiat (53.8%), followed by Firmicutes, and Actinobacteria. Estimates of fungal community composition showed Ascomycota as the dominant phylum. Presence of Zygomycota in marcha distinguishes it from the thiat. The results of NGS analysis revealed dominance of yeasts in marcha whereas molds out numbers in case of thiat. This is the first report on microbial communities of traditionally prepared amylolytic starters of India using high throughput sequencing.